The Surgeon - Wolfe, Leslie (Fiction writer) (New York : Grand Central, 2023)
"Trusted surgeon. Loving wife. Murderer? Before my world came crashing down, I had it all. The successful career I dreamed of. The beautiful red-brick home where I could relax in front of the fire. The handsome, devoted husband whose blue eyes and charming smile always made me feel safe. As I call time of death, my voice is steady. My colleagues stand hushed around me, their eyes on me, confused, concerned. I have never lost a patient until today. My hands tremble inside their gloves. I slide down the cold tiled walls, my heart racing in my chest. I have never hated a patient until today. But what choice did I have, once I recognized him? And what will I do to protect myself, if someone learns the truth?"--Provided by publisher.
Keywords: Women surgeons -- Fiction; Murder -- Fiction; Medical fiction; Psychological fiction; Thrillers (Fiction)